Small Circular Rep-Encoding Single-Stranded DNA Genomes in Peruvian Diarrhea Virome - Altan, Eda (2017)
Metagenomic analysis of diarrhea samples revealed the presence of numerous human enteric viruses and small circular Rep-encoding single-stranded DNA (CRESS-DNA) genomes. One such genome was related to smacoviruses, while eight others were related to genomes reported in the feces of different mammals. The tropism of these CRESS-DNA viruses remains unknown.